2023
DOI: 10.1002/ptr.7737
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin‐piperine co‐supplementation and human health: A comprehensive review of preclinical and clinical studies

Abstract: Curcumin is extracted from the rhizomes Curcuma longa L. It is known for its anti‐inflammatory and anti‐oxidant activities. Despite its safety and potential for use against various diseases, curcumin's utility is restricted due to its low oral bioavailability. Co‐administration of curcumin along with piperine could potentially improve the bioavailability of curcumin. The present review aimed to provide an overview of the efficacy and safety of curcumin‐piperine co‐supplementation in human health. The findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 125 publications
0
13
0
Order By: Relevance
“…41 Curcumin has been shown to have antibacterial properties since 1949, 42 and other studies have established its numerous pharmacological effects including anti-inflammatory, anticancer, anti-oxidant, wound-healing, and anti-viral activities, all of which are thought to have therapeutic benefits for a number of human-related ailments. [43][44][45][46][47][48][49][50][51][52][53][54] In vitro, curcumin inhibits many enzymes, including cyclooxygenase and the sarcoplasmic/reticulum calcium pump (SERCA). [55][56][57][58][59][60] The mechanisms of action associated with the use of curcumin in CF patients are depicted in Figure 5.…”
Section: Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Curcumin has been shown to have antibacterial properties since 1949, 42 and other studies have established its numerous pharmacological effects including anti-inflammatory, anticancer, anti-oxidant, wound-healing, and anti-viral activities, all of which are thought to have therapeutic benefits for a number of human-related ailments. [43][44][45][46][47][48][49][50][51][52][53][54] In vitro, curcumin inhibits many enzymes, including cyclooxygenase and the sarcoplasmic/reticulum calcium pump (SERCA). [55][56][57][58][59][60] The mechanisms of action associated with the use of curcumin in CF patients are depicted in Figure 5.…”
Section: Curcuminmentioning
confidence: 99%
“…Secondary metabolites of this component include phenolic acids, flavonoids, alkaloids, terpenoids, tannins, and saponins, each of which has been proven to have biological activity 41 . Curcumin has been shown to have antibacterial properties since 1949, 42 and other studies have established its numerous pharmacological effects including anti‐inflammatory, anticancer, anti‐oxidant, wound‐healing, and anti‐viral activities, all of which are thought to have therapeutic benefits for a number of human‐related ailments 43–54 . In vitro, curcumin inhibits many enzymes, including cyclooxygenase and the sarcoplasmic/reticulum calcium pump (SERCA) 55–60 .…”
Section: Herbal Medicinementioning
confidence: 99%
“…[15][16][17][18] Literature reviews have shown that, synergistic effect between piperine and curcumin, increasing the bioavailability of curcumin. [19,20] Additionally, recent reports also indicated that nanoparticles and piperine-loaded nanoparticles enhance the bioavailability of curcumin. [21,22] In research studies, curcumin derivatives are typically synthesized, and these synthetic derivatives, especially enone and dienone curcumin derivatives, have been noted for their superior antiangiogenic effects compared to curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated to possess a ′bioenhancer′ character [15–18] . Literature reviews have shown that, synergistic effect between piperine and curcumin, increasing the bioavailability of curcumin [19,20] . Additionally, recent reports also indicated that nanoparticles and piperine‐loaded nanoparticles enhance the bioavailability of curcumin [21,22] …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the anti‐diabetic and anti‐lipidemic effects of this polyphenol have previously been confirmed (Ganji et al, 2021; Mahdavi et al, 2020; Mahdavi, Bagherniya, et al, 2021; Mahdavi, Moradi, et al, 2021; Parsamanesh et al, 2018; Rafiee et al, 2021; Talebi et al, 2020). This phytochemical also has healing effects in many liver‐related diseases, including non‐alcoholic fatty liver disease (NAFLD), hepatic steatosis, and liver fibrosis (Bagherniya et al, 2018; Dadkhah Tehrani et al, 2023; Farzaei et al, 2018; Feng et al, 2019; Hassanizadeh et al, 2023; Heidari et al, 2023; Jalali et al, 2020; Lee et al, 2019; Sharifi et al, 2023; Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%